1981
DOI: 10.2307/1965996
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Women of Changing Marriage Transactions in Bangladesh

Abstract: Recent changes in marriage transactions in Bangladesh have led increasingly to a shift in the burden of marriage expenses from the groom's family of the bride. This reversal in the direction of wealth exchanges, which may not be in the best interest of the bride, reflects social and economic changes that have increased the income potential of the groom, which now surpasses previously valued attributes of the bride. In this paper, anthropologist Shirley Lindenbaum examines the effects of these changes on women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…If this were correct one might expect that dowry competition would have eased in recent years, as the rate of population growth has fallen sharply. A more nuanced version links this to modernisation, holding that it is the relative scarcity of grooms with the desirable quality of salaried employment which engenders competition (Lindenbaum 1981).…”
Section: Dowry In South Asiamentioning
confidence: 99%
“…If this were correct one might expect that dowry competition would have eased in recent years, as the rate of population growth has fallen sharply. A more nuanced version links this to modernisation, holding that it is the relative scarcity of grooms with the desirable quality of salaried employment which engenders competition (Lindenbaum 1981).…”
Section: Dowry In South Asiamentioning
confidence: 99%
“…There is a re-emphasis on dowries in marriage negotiations. Dowry has to be contextualised in the historical shifts in the region's political economy and resultant changes in social relations (Lindenbaum, 1981). Declining land productivity in Bangladesh through the 1970s and rising urban unemployment favours a salaried job-holder instead of a landowner in the choice of a groom.…”
Section: Migration and Conjugal Expectations In Rural Bangladesh 29mentioning
confidence: 99%
“…28 Traditionally, bride-price payments were practiced among the lower castes whereas dowry payments occurred within the upper castes (see, e.g., Blunt 1969;Srinivas 1978;Miller 1980). Additionally, there are numerous accounts of a transition from bride-price to dowry in the context of modernization (see, e.g., Lindenbaum 1981;Caldwell et al 1983;Billig 1992). These accounts fit well with the analysis here, where it will be demonstrated that development places an upward pressure on real marriage payments, turning formerly negative payments (or bride-prices) into positive payments (or dowries).…”
Section: Increasing Within-group Wealth Dispersionmentioning
confidence: 99%